PENGEMBANGAN USAHA DIVERSIFIKASI PRODUK PERIKANAN (NUGGET IKAN DAN TAHU BAKSO) DI KELOMPOK UMKM BUBULA KELURAHAN JAMBULA - Andriani, Rovina; Abdullah, Nursanti; Muchdar, Fatma; Juharni, Juharni; Suryani, Suryani; Yuliana, Yuliana; M. Irfan, M. Irfan; Leha, Alicia W; Ishak, Safira; Yusuf, Masri; Titaheluw, Syahnul Sardi (Jurnal Abdi Insani, 2024)
Diversification of processed fish into processed nugget and tofu meatball products is one of the new motivations to introduce to the Bubula Business group that fish which are usually fried, grilled, smoked, dried or cooked in whole form can be made into nutritious food or snacks that can be consumed by children. -children, adults and the elderly as well as diversification of processed fishery products such as fish nuggets and tofu-meatballs can be used as additional businesses to improve the economy of business groups. The objectives of this PKM activity are; 1). Introducing fish as a food ingredient that contains high nutritional aspects, 2). Provide an understanding of the benefits of fish for family health and children's intelligence, 3). Instill an interest in liking fish as daily food, 4). Increasing knowledge and skills in making diversified fishery products so as to increase consumption and the community's economy. This activity was carried out in July 2024 at the Bubula MSME Group, Jambula Village, involving 8 members of the Bubula MSME group and involving 6 Kubermas KKN students. The method used is conveying theory about fish nugget and meatball tofu products by distributing training modules to participants to facilitate understanding of the training material. This community service activity produces two new processed products, namely fish nuggets and meatball tofu which can provide many benefits for the Bubula MSME group, one of which is increasing the group's economic income and increasing fish consumption among families and the wider community. With training on the diversification of these two preparations for the Bubula MSME business group, it is hoped that it will become a new business to improve the family economy and increase fish consumption for all groups.